2024
DOI: 10.3390/su16031314
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Pre-Service Teachers’ Perspectives on the Integration of Digital Game-Based Learning for Sustainable STEM Education

Nonhlanhla Melody Gumbi,
Duduzile Sibaya,
Admire Chibisa

Abstract: Digitalization of STEM in higher education is envisioned to foster digital societies through enhanced contextualised engaged learning, digital skills, and access to digital learning resources, specifically in developing countries, including those in Africa. The dearth of empirical evidence validating digitalization hinders implementation. This study aims to investigate pre-service teachers’ perspectives towards the use of digital game-based learning (DGBL) for sustainable development of STEM education and prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
4
3
0
Order By: Relevance
“…The findings indicated that all four perception areas including perceived usefulness, ease of use, compatibility, and subjective norms yielded high ratings. This finding supported those of previous studies such as [56,58,69,72].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The findings indicated that all four perception areas including perceived usefulness, ease of use, compatibility, and subjective norms yielded high ratings. This finding supported those of previous studies such as [56,58,69,72].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, they believed that acquiring the essential knowledge and skills to integrate such technology was also straightforward. These findings validate previous studies conducted by [69,72].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…By cultivating a habit of reflection, pre-service teachers can become self-directed learners who continuously strive for excellence in teaching and learning (Schön, 1987). This emphasis on reflective practices aligns with the principles of social cognitive theory, which underscore the importance of self-reflection, selfefficacy beliefs, and goal setting in shaping behaviour and learning outcomes (Bandura, 1997;Gumbi et al, 2024). Thus, the findings highlight the synergistic relationship between reflective practices and problem-solving skills development, providing empirical support for the theoretical framework of social cognitive theory in the context of pre-service teacher education in South Africa.…”
Section: Discussionsupporting
confidence: 65%
“…Despite the recognition of the importance of problem-solving skills in teaching, research suggests that many pre-service teachers enter the profession with limited proficiency in this area (Darling-Hammond, 2006;Koehler & Mishra, 2020;Lundeberg et al, 1999;Nietfeld et al, 2006). Studies have identified various factors that contribute to pre-service teachers' difficulties in problem-solving, including limited content knowledge, lack of pedagogical expertise, and insufficient opportunities for authentic practice (Borko, 2004;Grossman et al, 2001;Gumbi et al, 2024;Lunenberg et al, 2007). Additionally, research has highlighted the need for pre-service teacher education programs to provide explicit instruction and support for the development of problem-solving skills rather than assuming that these skills will be acquired incidentally through classroom experiences (Fouche, 2024;Grossman et al, 2009;Kennedy, 1997;Zeichner, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%